2017
DOI: 10.7717/peerj.2810
|View full text |Cite
|
Sign up to set email alerts
|

Cryoelectrolysis—electrolytic processes in a frozen physiological saline medium

Abstract: BackgroundCryoelectrolysis is a new minimally invasive tissue ablation surgical technique that combines the ablation techniques of electrolytic ablation with cryosurgery. The goal of this study is to examine the hypothesis that electrolysis can take place in a frozen aqueous saline solution.MethodTo examine the hypothesis we performed a cryoelectrolytic ablation protocol in which electrolysis and cryosurgery are delivered simultaneously in a tissue simulant made of physiological saline gel with a pH dye. We me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Unfortunately, a problem exists when using cryosurgery; there is a range of temperatures and cooling rates of affected tissue and thus it is not uncommon for some of the target cells to survive treatment, thus a combination of electrolytic and freezing techniques was combined for this study. [26] This combination of electrolysis and cryosurgery has been dubbed cryoelectrolysis. An in vitro study of cryoelectrolysis on pig liver was the subject of testing where 3 tests were employed: a 10-minute cryosurgery only, a 10 minute EChT only, and a 10-minute freezing period was followed by electrolytic treatment of the pig liver.…”
Section: Echt Evolved: Echt In Tandem With Other Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, a problem exists when using cryosurgery; there is a range of temperatures and cooling rates of affected tissue and thus it is not uncommon for some of the target cells to survive treatment, thus a combination of electrolytic and freezing techniques was combined for this study. [26] This combination of electrolysis and cryosurgery has been dubbed cryoelectrolysis. An in vitro study of cryoelectrolysis on pig liver was the subject of testing where 3 tests were employed: a 10-minute cryosurgery only, a 10 minute EChT only, and a 10-minute freezing period was followed by electrolytic treatment of the pig liver.…”
Section: Echt Evolved: Echt In Tandem With Other Techniquesmentioning
confidence: 99%
“…Cryosurgery utilizes a needle‐like probe into a targeted tissue as a freezing interface propagates through surrounding tissue. Unfortunately, a problem exists when using cryosurgery; there is a range of temperatures and cooling rates of affected tissue and thus it is not uncommon for some of the target cells to survive treatment, thus a combination of electrolytic and freezing techniques was combined for this study . This combination of electrolysis and cryosurgery has been dubbed cryoelectrolysis.…”
Section: Advancements In Echtmentioning
confidence: 99%
“…Experiments with pH dyes in frozen gels, have shown that products of electrolysis can diffuse from the electrolysis electrode through the frozen media, at high subfreezing temperatures [ 29 ]. A subsequent study [ 30 ], simulated a cryoelectrolysis procedure in a gel. It was found that the products of electrolysis diffuse from the cryoelectrolysis probe (a conventional cryosurgery probe in which the metal body served also as the electrolysis electrode) outward during the early stages of freezing and throughout the thawing period.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were published on the concept of cryoelectrolysis [28][29][30][31][32]. First, a study was performed to determine if products of electrolysis can diffuse through a frozen media.…”
Section: Introductionmentioning
confidence: 99%